The Double-Edged Sword of Digital Connectivity: Advancing Society and Empowering Cybercriminals - ODESANMI, Akinola Festus; IBITOYE, Oladayo Aveez; IWELUMOR, Oluwakemi; OBUENE, Henry; AROWOLO, Oluwatosin Tobi; OLUSEGUN, Ilesanmi Daniel; DUROJAIYE, David (Ilorin Journal of Education, 2025)
Digital connectivity has significantly reshaped modern society, revolutionising how individuals communicate, access services, and conduct businesses. This transformation has promoted economic growth, improved productivity, and enhanced social inclusion. However, alongside these benefits, there has been an upsurge in cybercrime. This has led to palpable fear among individuals, organisations, and governments. This article, therefore, reviewed the double-edged sword of digital connectivity, its origin, impacts, and factors contributing to this crime. The study used secondary data, including websites, magazines, newspapers, books, articles and journals as an essential foundation for this study. To bridge the gaps from previous researchers, Social learning theory (SLT) was used to explain how individuals, their environment, and behaviours interact with others to engage in cybercriminal activities through observation, imitation, and reinforcement. It also presents a case study to examine the underlying factors contributing to cybercrime in Nigeria, offering insights into the socio-technical dynamics that enable its growth. Nevertheless, as dependence on digital technologies intensifies, the associated vulnerabilities to cyber threats have become increasingly complex and pervasive. Addressing this challenge necessitates a collaborative, multi-stakeholder approach encompassing governmental bodies, the private sector, academia, and civil society to maintain technological advancement and public trust.